Foreword to a scoping review of Interventions on fruit and vegetable intake in low-, middle-, and high-income countries: A global perspective - Hess, Sonja Y.; Olney, Deanna K. (SAGE Publications, 2025)
A healthy diet low in fat, sugars, and sodium and high in fruit and vegetables (F&V) is recommended to ensure overall health and reduce risk of noncommunicable diseases. However, despite the evidence of strong health benefits, dietary intake of both fruit and vegetables is inadequate in most populations worldwide. To better understand the state of the evidence of what has worked to improve F&V intake, we conducted a scoping review to summarize available evidence of interventions focusing on the impact on F&V intake, including those aiming to improve F&V intake specifically and those targeting diet, health, lifestyle or environment more broadly. We chose to take a global view as lessons learnt from studies in high-income countries may provide important insights for other contexts. The evidence summarized in this Food and Nutrition Bulletin supplement can be used to inform program and policy design as well as future research areas.